Trends in vaccination coverage against influenza in the pediatric population: an Italian overview. (20th October 2021) - Lanza, TE; D'Ambrosio, F; Messina, R; Pezzullo, AM; Villani, L; Rosano, A; Ricciardi, W; Cadeddu, C
Abstract: Background: Influenza is a major public health issue for its epidemiological, clinical and economic impact. Children are a relevant age group for the diffusion of the infection in the community as they shed the virus in greater amounts and for longer periods of time than adults of any age. Vaccination is the best strategy to fight the disease. In Italy, until last year, influenza vaccination for the pediatric population was offered free only to children in specific risk categories, while in the last season its was extended also to all subjects from 6 months to 6 years old. The purpose of this work is to analyze the trend of vaccination coverage among children in the last decade in Italy. Methods: We retrieved vaccination coverage data by the Italian Ministry of Health relating to influenza vaccination in the age groups 0-2, 2-4, 5-8 and 9-14 in the years 2010-2020 and analysed trends in and between regions. Results: A preliminary analysis shows that vaccination coverage in the age groups considered ranged from a minimum of 1.1% to a maximum of 4.5%. The highest average percentage reached was recorded in the season 2010-11 (3.8%), while the lowest in the 2015-16 (1.5%). The highest average values (12, 9%; 10, 5%) were found in Puglia and Toscana, while the lowest (0.3%) in Friuli Venezia Giulia. From 2010 to 2015 there was a progressive decline in vaccination coverage, while in the following years there was a slight increase, up to the year 2019-2020, in which the average percentage value was 3%. Further results are expected for next summer, when 2020-21 data will be available. Conclusions: Our analysis shows that in the Italian regions influenza vaccination coverage in children is variable but still extremely low. Childhood vaccination could provide an opportunity to decrease the burden of disease in this age group but may also help to protect the population at risk of serious complications, such as the elderly, due to the social role children play in the spread of this virus. Key messages: Influenza vaccination in children is a major public health issue. Additional efforts are needed to make vaccination available for children and improve the stakeholders' awareness on this topic.